Secular changes in physical growth and obesity among southwestern American Indian children over four decades. Issue 2 (6th December 2016) - Vijayakumar, P.; Wheelock, K. M.; Kobes, S.; Nelson, R. G.; Hanson, R. L.; Knowler, W. C.; Sinha, M.
Summary: Background and Objectives: Most studies describing childhood obesity in the United States are based on cross‐sectional surveys and do not include substantial numbers of American Indians (AI). Secular trends in height and weight reflect general health status. This study describes weight trends and transitions among AI children over a 43‐year period. Methods: Anthropometric data were obtained from a prospective study conducted in a southwestern US AI population (1965 through 2007). For cross‐sectional analysis, 12 377 observations were available from 6529 children across four birth cohorts (1955–1964, 1965–1974, 1975–1984, 1985–1994). Participants were stratified into three age groups: pre‐ (5–9 years), early (10–13) and late (14–17) adolescence. Longitudinal analyses included 1737 children with one exam in each age group. Results: In early and late adolescence, weight increased across birth cohorts. Prevalence of obesity among pre‐adolescents was 17.5% (95% CI, 15.1%–19.9%) in the 1955–1964 cohort and 33.7% (95% CI, 30.1%–36.4%) in the 1985–1994 cohort. 74% of children overweight in pre‐adolescence in the 1985–1994 cohort became obese by late adolescence; in the 1955–1964 cohort, only 43% made this transition. Conclusions: This study describes the rising prevalence of childhood obesity. Children obese in pre‐adolescence remained obese in late adolescence, stressing the need for early intervention.